2020
DOI: 10.1055/s-0040-1715846
|View full text |Cite
|
Sign up to set email alerts
|

Routine Multidisciplinary Review of Severe Maternal Morbidity Is Associated with a Reduction in Preventable Cases of Severe Maternal Morbidity

Abstract: Objective Severe maternal morbidity (SMM) has increased by 45% in the United States and is estimated to affect up to 1.5% of all deliveries. Research has not yet been conducted that demonstrates a benefit to multidisciplinary review of SMM. The aim of our study was to determine if standardized, routine review of the cases of SMM by a multidisciplinary committee results in a reduction of potentially preventable cases of SMM. Study Design A retrospective cohort study of all women admitted for deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Routine systematic review of SAMM, by a multidisciplinary team (MDT), has been shown to reduce potentially preventable events. 17 Contributing factors, identified during detailed case review, are most commonly associated with professional and system-level care factors. 18 This provides an avenue for practice changes to target gaps in care and improve outcomes.…”
Section: Samm Review Processesmentioning
confidence: 99%
“…Routine systematic review of SAMM, by a multidisciplinary team (MDT), has been shown to reduce potentially preventable events. 17 Contributing factors, identified during detailed case review, are most commonly associated with professional and system-level care factors. 18 This provides an avenue for practice changes to target gaps in care and improve outcomes.…”
Section: Samm Review Processesmentioning
confidence: 99%